EFFICACY OF DRUG THERAPY IN PATIENTS WITH PERIPHERAL ARTERIAL DISEASE IN RELATION TO SMOKING - Stepanovic, Nemanja; Damnjanovic, Zoran; Jovanovic, Nemanja (Acta medicae Medianae, 2024)
Peripheral arterial disease is one of the manifestations of atherosclerosis that manifests itself primarily in the peripheral arteries of the lower extremities and the aorto-iliac segment. The largest number of patients, about 90%, have functional ischemia (Stage IIa and IIb according to Fontaine). For these patients, the therapy of choice is medication consisting of a combination of acetylsalicylic acid, cilostazol and pentoxifylline. Smoking is a very significant risk factor for the development of peripheral arterial disease and is also one of the most significant outcome modifiers. The study included 82 patients diagnosed with functional ischaemia of the lower extremities treated at the Clinic of Vascular Surgery of the Clinical Center in Niš, starting from January 2020 to December 31, 2020. Smoking was present in 76.82% of respondents. In the research conducted, 48.78% of respondents used pentoxifylline + acetylsalicylic acid, while 51.22% of respondents were treated with cilostazol + acetylsalicylic acid. Results showed the extension of the claudication distance after 6 months was significantly greater in the group of patients who used cilostazol + acetylsalicylic acid. In a subgroup of patients smoking > 20 cigars daily and with > 20 years of smoking there was a significant increase in claudication distance after 6 months in the cilostazol + acetylsalicylic acid group compared to pentoxifylline + acetylsalicylic acid group. In conclusion, the number of cigarettes/day and length of smoking experience have a significant effect on the applied therapeutic modality in patients with peripheral arterial disease. Cilostazol + acetylsalicylic acid therapy was more effective than pentoxifylline + acetylsalicylic acid.